Peningkatan Kualitas Pembelajaran Menulis Narasi Ekspositorik Dengan Menggunakan Media Digital - Novi Talentina Lumban Gaol; Putri Angelina Sirait; Pebri Peronika Sinaga (Jurnal Diferensiasi Pendidikan, 2026)
This study aims to improve the quality of learning in writing expository narratives through the use of digital media for elementary school students. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages implemented in two cycles. The participants were elementary school students who experienced difficulties in developing ideas and organizing expository narrative texts. Data were collected through observation, writing tests, interviews, and documentation, then analyzed using descriptive quantitative and qualitative techniques. The findings indicate that the use of digital media significantly improved students' writing skills, learning motivation, classroom participation, and engagement. The average writing score increased from 58.3 in the pre-cycle to 75.4 in Cycle I and 81.2 in Cycle II. Learning mastery also improved from 65% to 89%. Furthermore, digital media created a more interactive learning environment that facilitated students in generating ideas, organizing paragraphs, and applying appropriate language conventions in expository narrative writing. Therefore, digital media can serve as an effective and innovative instructional medium for improving the quality of Indonesian language learning, particularly in teaching expository narrative writing at the elementary school level.